Household Saving in France : Stochastic Income and Financial Deregulation - Levy, Joaquim (IMF Working Papers; Working Paper ;, 1994)
The household saving ratio in France has undergone very sharp changes over the past two decades, falling dramatically in the first part of the 1980s before rising in more recent years. This paper emphasizes two factors in the evolution of private saving in France. The first relates to perceptions of household income growth and uncertainty, which are likely to have been affected by deteriorating labor market conditions, and which may therefore help to account for the recent increase in saving. The second factor relates to financial deregulation which may have lowered saving and increased its sensitivity to interest rate changes. It is argued that both factors have played some role in the evolution of French household saving.